2011
DOI: 10.1186/1471-244x-11-97
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of severe mental distress and its correlates in a population-based study in rural south-west Uganda

Abstract: BackgroundThe problem of severe mental distress (SMD) in sub-Saharan Africa is difficult to investigate given that a substantial proportion of patients with SMD never access formal health care.This study set out to investigate SMD and it's associated factors in a rural population-based cohort in south-west Uganda.Methods6,663 respondents aged 13 years and above in a general population cohort in southwestern Uganda were screened for probable SMD and possible associated factors.Results0.9% screened positive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…For Nigeria, a low prevalence of 2.7% in current smoking was reported in 2008[ 16 ] compared to 14.6% reported one year previously (2007). [ 25 ] the smoking prevalence previously reported in rural Uganda during 2008–2009 (2.2%)[ 31 ] increased slightly to 6% in 2011. [ 17 ]…”
Section: Resultsmentioning
confidence: 99%
“…For Nigeria, a low prevalence of 2.7% in current smoking was reported in 2008[ 16 ] compared to 14.6% reported one year previously (2007). [ 25 ] the smoking prevalence previously reported in rural Uganda during 2008–2009 (2.2%)[ 31 ] increased slightly to 6% in 2011. [ 17 ]…”
Section: Resultsmentioning
confidence: 99%
“…About a tenth (7.3%) of the respondents self- reported that they had ever suffered from a nervous or psychiatric problem of these only 8% reported that they had ever sought treatment for this condition from a health facility indicating that many of such cases are not reported to the modern health system. Kinyanda and colleagues in non-war affected south-western Uganda reported a prevalence of self-reported severe mental illness of 0.9% [ 27 ]. Other Ugandan studies [ 38 , 39 ] have noted that less than 20% of all persons with mental illness are treated at formal health services in the country.…”
Section: Discussionmentioning
confidence: 99%
“…A structured questionnaire consisting of various standardized tools previously employed in the Ugandan context by one of the investigators (EK) was used in this study [ 19 , 26 , 27 ]. The different assessment tools in the study questionnaire we translated into the local Luo language by a process of forward and backward translation by two teams of mental health professionals working independently of each other.…”
Section: Methodsmentioning
confidence: 99%
“…This study has found a link between behavioral problems, both externalized and total, and an antiepileptic treatment prior to the consultation at the CSMT. In non epileptic patients, Kinyanda et al [19] and Abbo et al [20] had found that type of treatment, biomedical and/or traditional, influences psychological issues. In the present study, behavioral problems were less frequent in CWE who had not received antiepileptic treatment prior to the consultation at the CSMT.…”
Section: Factors Associated With Behavioral Problemsmentioning
confidence: 99%